Visualization Animal Tissue: Development of a 3D E-Atlas Based on Problem-Based Learning with a Deep Learning Approach in High School - Ayu Tryani, Salsa Belia; Fauziah, Nurul; Hidayati, Nurkhairo; Putri, Iffa Ichwani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a 3D E-Atlas based on Problem-Based Learning (PBL) and an in-depth learning approach for teaching animal tissue at the senior high school level and to evaluate its validity and practicality. The study employed a Research and Development (R&D) method using the Plomp development model, which encompasses the preliminary investigation and prototyping stages. The research participants consisted of 67 Grade 11 students from two senior high schools in Riau Province, Indonesia. Data were collected through interviews, needs analysis questionnaires, expert validation sheets, and student practicality questionnaires. The development process involved curriculum analysis, instructional analysis, interviews, needs assessment, self-evaluation, expert feasibility testing, one-to-one evaluation, small-group evaluation, learner practicality testing, and documentation. The findings indicated that the developed 3D E-Atlas achieved a very high level of validity, as reflected in an expert validation score of 97%. Furthermore, the practicality test indicated that the media was categorized as very practical, with a score of 85% in the field test. These findings suggest that the integration of interactive 3D visualization with PBL syntax and immersive learning activities may support students’ learning motivation, engagement, and conceptual understanding of animal tissue. The contribution of this study lies in the development of innovative digital learning media for biology education by integrating 3D visualization technology with a student-centered learning approach to support interactive, contextualized, and meaningful 21st-century learning.